2021
DOI: 10.1038/s41398-020-01182-w
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic features of recurrent major depressive disorder in remission, and the risk of future recurrence

Abstract: Recurrent major depressive disorder (rMDD) is a relapsing-remitting disease with high morbidity and a 5-year risk of recurrence of up to 80%. This was a prospective pilot study to examine the potential diagnostic and prognostic value of targeted plasma metabolomics in the care of patients with rMDD in remission. We used an established LC-MS/MS platform to measure 399 metabolites in 68 subjects with rMDD (n = 45 females and 23 males) in antidepressant-free remission and 59 age- and sex-matched controls (n = 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Of the included studies (Table 1), three were development and external validation studies, [28][29][30] eight were development-only studies 25,[31][32][33][34][35][36][37] and one 24 was an external validation study. Three 25,35,36 of the development-only studies reported internal validation. No prognostic model was externally validated in more than one included study and, therefore, a meta-analysis was not necessary.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies (Table 1), three were development and external validation studies, [28][29][30] eight were development-only studies 25,[31][32][33][34][35][36][37] and one 24 was an external validation study. Three 25,35,36 of the development-only studies reported internal validation. No prognostic model was externally validated in more than one included study and, therefore, a meta-analysis was not necessary.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Most commonly, these were disease-related characteristics and demographic factors. Some studies explored some less common predictors such as: neuropsychological predictors (emotional categorisation, emotional memory, and facial expression recognition); 36 personality characteristics such as neuroticism; 32 psychosocial predictors such as life stress and interpersonal difficulties; 31 biochemical predictors such as results from the corticotrophin-releasing factor test; 37 peripheral blood metabolomic markers; 35 and combinations of items from the Symptom Checklist (SCL-90). 34 Of the 11 development studies, nine used regression analysis (five used logistic regression 30,[32][33][34]37 and four used Cox proportional hazards regression to study time to recurrence.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In contrast, on a different cohort of MDD patients undergoing 6 weeks of paroxetine treatment, low DHA was associated with non‐response (R. J. Mocking et al, 2015). Other clinical studies have shown significant associations between fatty acids and antidepressant response (T. Dinan et al, 2009; R. J. T. Mocking et al, 2021); however, it is challenging to compare them due to different technical approaches, sample sizes and type of antidepressant drug administered.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors did not observe any statistically significant difference in inosine plasma levels between the remitted and non-remitted groups ( Ali-Sisto et al, 2016 ). On the other hand, Mocking et al (2021) demonstrated that inosine plasma levels were decreased in both males and females with recurrent major depressive disorder in remission. Zhou et al (2019) studied the potential biomarkers of depression in children and adolescents with MDD.…”
Section: Inosine and Depressionmentioning
confidence: 99%